2016
DOI: 10.3390/ma9080707
|View full text |Cite
|
Sign up to set email alerts
|

Coating and Patterning Functional Materials for Large Area Electrofluidic Arrays

Abstract: Industrialization of electrofluidic devices requires both high performance coating laminates and efficient material utilization on large area substrates. Here we show that screen printing can be effectively used to provide homogeneous pin-hole free patterned amorphous fluoropolymer dielectric layers to provide both the insulating and fluidic reversibility required for devices. Subsequently, we over-coat photoresist using slit coating on this normally extremely hydrophobic layer. In this way, we are able to pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…Given a response time of < 20 ms per drop (Figure 2d), the device can harvest this energy within less than 1/2 h. The fabrication of the substrates is based on standard fabrication processes from the semiconductor and display industries. [43] It is therefore highly parallel provided that the Pt wire in our experiments is replaced by deposited or printed electrodes on the substrate. Further optimization of the dielectric stack may lead to even further increases in efficiency.…”
mentioning
confidence: 99%
“…Given a response time of < 20 ms per drop (Figure 2d), the device can harvest this energy within less than 1/2 h. The fabrication of the substrates is based on standard fabrication processes from the semiconductor and display industries. [43] It is therefore highly parallel provided that the Pt wire in our experiments is replaced by deposited or printed electrodes on the substrate. Further optimization of the dielectric stack may lead to even further increases in efficiency.…”
mentioning
confidence: 99%
“…Chen et al 11 also successfully fabricated a poly(imide siloxane) hydrophobic insulator layer on ITO glass based on screenprinting technology, and the resulting large-area EWD exhibited good switch performance and relatively high yield. Furthermore, the technological barrier of a glass substrate, instead of a exible substrate such as polyethylene terephthalate or paper, lies in the difficulty of the temperature limitation during the fabrication process of EWDs because the curing temperature of traditional hydrophobic material is higher than 200 C. 10 Kim and Steckl 12 built electrowetting structures, including a metal ground electrode, dielectric layer, and uoropolymer layer, on Sappi paper. They found that the resulting electrowetting device on paper could attain a contact angle change in ambient oil, with a fast switching time of 20 ms.…”
Section: Introductionmentioning
confidence: 99%
“…Electrowetting (EW) refers to the phenomenon of altering the surface wettability of an electrode or dielectric layer with an applied electric field [1,2]. As an approach to manipulating minute fluids, electrowetting has attracted a great deal of attention for its application within reflective display devices [3,4], lab-on-a-chip systems [5,6], and optic lenses [7,8]. The basis of modern electrowetting was first described in detail by G. Lippmann in 1875 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient dielectric strength leads to a breakdown of the dielectric layer before it reaches the working voltage [18], and a hydrophobic dielectric layer surface is required for larger variations of the contact angle. Amorphous fluoropolymers have often been applied as insulating and hydrophobic layers [4,15,19] or as hydrophobic top coatings combined with inorganic insulating layers beneath. The inorganic materials used for insulating coatings include SiO 2 , TiO 2 , Si 3 N 4 , Al 2 O 3 , etc.…”
Section: Introductionmentioning
confidence: 99%